Japan work ways 1960 - 1976 - 1990 - Takezawa, Shin-ichi (Japan Institute of Labour, 1981)
This book introduce about industrial relations since 1945. Managemetn enemy or partner. Acceptance of managemetn authority. Community relations in the company. Commitment to the company.